Tradisi Ngemblok dan Praktik Pernikahan Dini: Studi Kasus di Desa Gilis, Rembang, Indonesia - Siti Nor Kholisoh; Misroh Sulaswari (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The Ngemblok tradition is closely linked to the continuation of early marriage practices in several areas, including Desa Gilis, Sarang, Rembang, Indonesia. This study aims to: (1) examine the role of Ngemblok in shaping and preserving early marriage; (2) explore community views on this practice; and (3) identify the village government’s role in addressing early marriage. Using a qualitative case study approach, data were collected through observation, interviews, and documentation, then analyzed via data reduction, presentation, and conclusion drawing. Findings show that Ngemblok plays a key role in maintaining early marriage, as it is part of social norms and a survival strategy amid economic pressures and limited education access. The tradition acts as a form of protection and social control over adolescent girls but encourages marriage before psychological and economic maturity. Community opinions vary: some support it for moral and cultural reasons, while others recognize negative impacts like school dropouts and family instability. The village government has made efforts through counseling, youth empowerment, skills training, and children’s forums to change mindsets and reduce early marriage. However, change is difficult because Ngemblok is deeply rooted as a symbol of honor, cultural identity, and important social capital in the local society.